Evaluation of an immunochromatography-based rapid antigen test, Inspecter Kowa® SARS-CoV-2, using saliva specimens for the detection of SARS-CoV-2. Issue 6 (June 2023) - Kodana, Masahiro; Orihara, Yuta; Tezuka, Mariko; Takahashi, Rina; Noguchi, Sakiko; Matsuzaki, Nanako; Takada, Tomohito; Kobari, Naomi; Ogane, Kana; Kawamura, Rieko; Kawamura, Toru; Takeuchi, Shinichi; et al.
Abstract: Background: In the context of the coronavirus disease 2019 (COVID-19) pandemic, a rapid and reliable point-of-care test is an essential tool for controlling the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In particular, an immunochromatography test (ICT) that uses saliva specimens for rapid antigen detection not only reduces the risk of secondary infections but also reduces the burden on medical personnel. Methods: The newly developed salivary antigen test kit "Inspecter Kowa® SARS-CoV-2" is an ICT to which saliva specimens can be directly applied. We evaluated its usefulness in comparison with reverse transcription quantitative PCR (RT-qPCR) and the Espline® SARS-CoV-2 Kit for the detection of SARS-CoV-2 using nasopharyngeal swab specimens. In this study, 140 patients with suspected symptomatic COVID-19 who visited our hospital were enrolled, and nasopharyngeal swab and saliva specimens were collected after they consented to participate in the study. Results: Inspector Kowa SARS-CoV-2 was positive in 45 of 61 (73.8%) saliva that were positive by RT-qPCR and the Espline® SARS-CoV-2 Kit was also positive in 56 of 60 (93.3%) Np swabs that were positive by RT-qPCR. Good antigen detection was achieved by ICT with saliva and nasopharyngeal swab specimens when viral load was ≥10 5 copies/mL, whereas detection sensitivity was low when viral load was <10 5 copies/mL, especially in saliva specimens. Conclusion: This ICT for the detection of SARS-CoV-2 salivary antigen is an attractive tool that does not require specialized equipment and allows patients to perform the entire process from sample collection to self-diagnose and to reduce the burden on medical care during a pandemic.